1999
DOI: 10.1074/jbc.274.31.21932
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channel Activity of the BH3 Only Bcl-2 Family Member, BID

Abstract: BID is a member of the BH3-only subgroup of Bcl-2 family proteins that displays pro-apoptotic activity. The NH 2 -terminal region of BID contains a caspase-8 (Casp-8) cleavage site and the cleaved form of BID translocates to mitochondrial membranes where it is a potent inducer of cytochrome c release. Secondary structure and fold predictions suggest that BID has a high degree of ␣-helical content and structural similarity to Bcl-X L , which itself is highly similar to bacterial pore-forming toxins. Moreover, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
2
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(129 citation statements)
references
References 29 publications
3
120
2
4
Order By: Relevance
“…Recombinant Bcl-2 can form channels in planar bilayers. 45,48 In contrast, no new channel activities are detected when Bcl-2 is overexpressed in FL5.12 or MDA-231 cells, suggesting that this protein does not form channels in native mitochondrial membranes. 20,51 However, channels whose conductance is between 0.75 and 1 nS are detected in isolated mitochondria after addition of caspase-cleaved recombinant Bcl-x L (DN-Bcl-x L ).…”
Section: Regulation Of Mac By the Antiapoptotic Proteinsmentioning
confidence: 97%
See 2 more Smart Citations
“…Recombinant Bcl-2 can form channels in planar bilayers. 45,48 In contrast, no new channel activities are detected when Bcl-2 is overexpressed in FL5.12 or MDA-231 cells, suggesting that this protein does not form channels in native mitochondrial membranes. 20,51 However, channels whose conductance is between 0.75 and 1 nS are detected in isolated mitochondria after addition of caspase-cleaved recombinant Bcl-x L (DN-Bcl-x L ).…”
Section: Regulation Of Mac By the Antiapoptotic Proteinsmentioning
confidence: 97%
“…50 Unlike Bax and Bak, antiapoptotic Bcl-2 family proteins and t-Bid only form large-conductance channels when they are assayed or pre-inserted at low pH (Table 2). 45,48 Importantly, no channel activity has been detected that can be attributed to Bcl-2 in mitochondria of cells overexpressing this protein. 20,51 These observations raised questions concerning the physiological relevance of channels formed by the antiapoptotic and 'BH3 domain-only' members of the Bcl-2 family.…”
Section: Channel-forming Properties Of Bcl-2 Family Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has also been suggested that t-Bid forms membrane-inserted homotrimers that do not interact with other mitochondrial proteins (Grinberg et al, 2002). Moreover, t-Bid can form channels in planar lipid bilayers (Schendel et al, 1999) and destabilize them (Kudla et al, 2000). The question of whether t-Bid's effects on mitochondria depend on interactions with sessile mitochondrial proteins, including a CsA target, has been controversial .…”
Section: Mitochondrial Membrane Permeabilization: the Central Event Omentioning
confidence: 99%
“…[9][10][11][12] . The ability of Bax to form ion-conducting pores in synthetic and mitochondrial membranes suggests that such pores are involved in the release of cytochrome c. [13][14][15] Bax however might work as a twin-arginine translocation (Tat)-like protein rather than as an always-open ion-conducting pore in the OMM.…”
mentioning
confidence: 99%